DNA metabarcoding to estimate diet overlap between the introduced Joro spider (Trichonephila clavata) and three native orb-weaving spiders - Erin E. Grabarczyk; Jason M. Schmidt (PLoS ONE, 2026)
The introduction of novel generalist predators to new ecosystems can dramatically alter species interactions and established food webs. Invasive predators may contribute to pest control services; however, a net loss of biodiversity can occur if invasives displace natives through intraguild predation or resource competition. Joro spiders ( Trichonephila clavata ) are an introduced, orb-weaving spider that show rapid range expansion in the United States. Trophic patterns of orb-weaving spiders are largely unknown, and as such, the impact of Joro spiders on established food webs is unclear. We explored patterns of diet composition and prey overlap between Joro spiders and three co-occurring, native orb-weaving species with molecular gut content analysis. In addition, we asked whether the composition of focal native spider diets differed at sites co-inhabited by Joro spiders. We collected female spiders from 52 sites within the Joro spider’s introduced range and analyzed gut content via DNA metabarcoding and high-throughput Illumina sequencing. Despite overlap in many prey taxa consumed, overall diet composition was dissimilar between Joro and native spiders. Joro spider diets were distinct, with at least 26 unique prey taxa not detected in native spider diets. Moreover, native spider diets were similar regardless of whether Joro spiders were present at collection sites. Thus, our initial analysis suggests that while Joro spider diets do overlap with native spiders, their use of many unique food resources does not suggest strong competition. Additional research into web placement and spatial overlap as mechanisms underlying Joro spider invasion success should help clarify the potential for exclusion of native predator populations.